Removal of Chromium (III) from Aqueous Solution by Coconut Husk and Rice Straw - Tan, W. T.; Choong, N. Y.; Lee, C. K. (Universiti Putra Malaysia Press, 1993)
Coconut husk fibre and rice straw were found to be able to remove significant amount of Cr (III) ions from aqueous solutions. Its removal is a function of pH and concentration. The optimum pH range for maximum uptake is between 4 and 6 for both substrates. The adsorption capacity was found to be 0.55 and 0.30 millimole Cr (III) / g substrate for coconut husk and rice straw respectively. The adsorption kinetic studies show that the removal process follows a first order rate expression. The breakthrough curves and adsorption efficiency of various columns containing mixed media of coconut husk/rice straw, soil and sand have been obtained. The results demonstrate that these agricultural residues could be used as barriers in a landfill to maximize immobilization of toxic metal ions such as Cr (III) in leachates.